The crystal structure of R-2′-amino-N-methyl-N-(1-phenylethyl)-[1,1′-biphenyl]-4-carboxamide, C22H22N2O - Yao Yi; Liang Jia-Jun; Wang Hai-Ping (Zeitschrift für Kristallographie - New Crystal Structures)
C22H22N2O, orthorhombic, P212121, a = 7.09830(10) Å, b = 13.8691(2) Å, c = 18.1492(3) Å, V = 1786.76(5) Å3, Z = 4, R gt(F) = 0.0386, wR ref(F 2) = 0.1078, T = 300 K.